Effects of Stepwise Carbetocin Administration on Postpartum Hemorrhage after Prelabor Cesarean Delivery - Punyaniti Buppawong; Tripop Lertbunnaphong; Pattarawan Limsiri; Anisa Phetses; Patchareya Nivatpumin; Namtip Triyasunant (Siriraj Medical Journal, 2025)
Objective: To evaluate the effectiveness of stepwise administration of carbetocin in reducing postpartum hemorrhage (PPH) in term pregnancies undergoing elective cesarean delivery.